1992
DOI: 10.1007/bf00227250
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting of fusimotor neurones after partial denervation of the cat soleus muscle

Abstract: Normally, gamma motoneurones innervate only the intrafusal fibres of muscle spindles. This is a report of sprouting of gamma motoneurones to innervate extrafusal muscle fibres following partial denervation of the soleus muscle of kittens. In eight newborn animals, the L7 ventral root was cut on one side under anaesthesia and the animals were then allowed to recover. At approximately 100 days of age animals were reanaesthetised and a study made of mechanical properties of motor units whose axons ran in the S1 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this regard, our data from the long‐term evaluation of Patient 5 and 6 might be tentatively interpreted taking into account that the reinnervation of intrafusal fibers after partial denervation is a long and defective process. Gamma‐motoneurons may sometimes sprout to innervate extrafusal fibers, thus leaving the muscle spindle without motor drive 33…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our data from the long‐term evaluation of Patient 5 and 6 might be tentatively interpreted taking into account that the reinnervation of intrafusal fibers after partial denervation is a long and defective process. Gamma‐motoneurons may sometimes sprout to innervate extrafusal fibers, thus leaving the muscle spindle without motor drive 33…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this twofold mechanism, the toxin should reduce the TVR more than the M‐max. Because the reinnervation of intrafusal fibres is a long and defective process [10], the TVR reduction should also last longer than the M‐max reduction. The difference between the BoNT‐A‐induced reduction of the TVR and the M‐max could therefore be the physiological marker of the toxin’s action at the level of the pre‐synaptic terminal of the γ‐motoneurons.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that sensory axons can also release acetylcholine (Falempin et al 1989). Fusimotor neurons in extensively denervated muscles have been observed to sprout and innervate extrafusal fibers (Einsiedel et al 1992). Thus, a sensory nerve, with some fibers resembling motor nerves, may be capable of preserving a degree of muscle bulk in a muscle flap with no other physical stimulation.…”
Section: Discussionmentioning
confidence: 99%